Effect of Oak Chip Addition at Different Winemaking Stages on Phenolic Composition of Moravia Agria Red Wines - Gómez Gallego, M.A.; Sánchez-Palomo, E.; Hermosín-Gutiérrez, I.; González Viñas, M.A. (South African Journal of Enology and Viticulture, 2016)
This study compared changes in the phenolic composition of Moravia Agria wine and its effect on colour, co-pigmentation as well as on physicochemical properties, such as antioxidant capacity, caused by adding oak chips at different stages of the winemaking process. Moravia Agria control wine was made following traditional winemaking processes, without oak chips. Oak chips were added to the rest of the wines at two dose rates (3 and 6 g/L) at different stages of the winemaking process: for one week during alcoholic fermentation, during malolactic fermentation and in young red Moravia Agria wine. Only slight significant differences were found in phenolic composition, antioxidant activity and chromatic characteristics between the Moravia Agria wines treated with oak chips and the control wine. However, oak chip addition slightly decreased the content of non-polymeric red pigments (monomeric anthocyanins and pyranoanthocyanins) and also of resveratrol-monomer stilbenes. It is suggested that oak chip addition to Moravia Agria wines can be selected as part of the targeted sensory profile (relative intensity of sensory descriptors provided by grape and oak wood), since only a few changes have been observed in the phenolic profiles, antioxidant capacity value and colour characteristics.